High-temperature-resistant and high-humidity-resistant polyisocyanate composition and preparation method thereof

Through the copolymerization reaction of aliphatic diisocyanate and alkoxysilane monoisocyanate, a polyisocyanate composition is formed, which solves the problem of polyurethane material failure in high temperature and high humidity environment, and achieves efficient and stable mechanical properties. It is suitable for sealants and automotive hood paints.

CN119591836AActive Publication Date: 2025-03-11WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202411746091.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-11
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Existing polyurethane materials are prone to foaming and delamination failure in high temperature and high humidity environments, and high viscosity affects the wetting of the substrate interface, making it difficult to use in such environments for a long time.

Method used

Copolymerization of aliphatic diisocyanate and alkoxysilane monoisocyanate is used to form a polyisocyanate composition containing a mononuclear structure of silicon isocyanurate. The alkoxysilane is introduced through chemical bonds to improve the bonding and mechanical properties.

Benefits of technology

It significantly improves the construction efficiency and the comprehensive mechanical properties of the products, especially in high temperature and high humidity environments, and is suitable for polyurethane sealant or automotive gloss paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163765470000021
    Figure BDA0005163765470000021
  • Figure BDA0005163765470000081
    Figure BDA0005163765470000081
  • Figure FDA0005163765460000011
    Figure FDA0005163765460000011
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant and high-humidity-resistant polyisocyanate composition and a preparation method thereof. The polyisocyanate composition comprises a mononuclear body structure which is formed by aliphatic diisocyanate and alkoxy silane monoisocyanate and contains silicon group isocyanurate, and the mononuclear body structure is formed by aliphatic diisocyanate and alkoxy silane monoisocyanate. The isocyanate composition provided by the invention has the advantages of no addition of a solvent, low viscosity, excellent stability in a high-temperature and high-humidity environment and simple manufacturing process, and is especially suitable for the fields with complex and changeable use environments and longer service life, such as the fields of coatings and adhesives in the automobile industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of isocyanates, and in particular relates to a high temperature and high humidity resistant polyisocyanate composition and a preparation method thereof. Background Art

[0002] Polyurethane resin is a general term for macromolecular compounds containing repeated carbamate groups on the main chain. It can be widely used in many fields such as coatings, adhesives, sealants, elastomers, foams and reinforced composite materials. Especially in the field of automotive coatings or structural adhesives, the polyurethane products formed are expected to have high mechanical strength, strong adhesion to the substrate and excellent weather resistance. Although ordinary polyurethane has good mechanical properties and excellent wear resistance, it often needs to be primed for the bonding and adhesion of materials, and is prone to foaming and delamination failure, especially in high temperature and high humidity environments.

[0003] In recent years, some studies have attempted to use silicone-based resins to modify polyurethane products, but there are still many problems to be solved.

[0004] The technical solution of CN105482758A adopts the reaction of a polyurethane prepolymer with a terminal NCO and phenylaminomethyltriethoxysilane to obtain a silane-terminated polymer. However, this technical solution has a slow reaction speed and the steric hindrance effect of the benzene ring will make the end-capping incomplete, thereby affecting the final performance of the product. In addition, its excessively high viscosity affects the wetting of the substrate interface and cannot prevent damage by moisture.

[0005] CN117384579A uses mercaptopropyl trimethoxysilane and hydroxyethyl methacrylate to react with the initiator azobisisobutyronitrile to form a modified silane coupling agent, and then reacts with a polyurethane prepolymer until the product does not contain NCO groups. The product can introduce the organic silane structure into the polyurethane by chemical bonds through the reactive groups, so that the tensile strength and elongation at break of the product are improved. However, the process is complicated, and all the NCO groups are reacted, which makes it difficult to achieve further thermal crosslinking or wet crosslinking reactions, and cannot be used for a long time in a high temperature and high humidity environment.

[0006] In summary, there is an urgent need for a polyisocyanate composition containing a siloxane group which is solvent-free, has low viscosity and has excellent comprehensive mechanical properties. Summary of the invention

[0007] One of the purposes of the present invention is to provide a polyisocyanate composition containing a siloxane group. The composition has the advantages of being solvent-free and having low viscosity, and can significantly improve the construction efficiency and the comprehensive mechanical properties of the product. In particular, it is found that the product prepared by the composition has excellent performance stability under high temperature and high humidity environment.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] A polyisocyanate composition containing a siloxane group, wherein the polyisocyanate composition comprises a silicon-based isocyanurate mononuclear structure formed by an aliphatic diisocyanate and an alkoxysilane monoisocyanate, such as Formula I:

[0010]

[0011] Among them, R1 is the residual group of aliphatic diisocyanate after removing the isocyanate group, R2 is an alkyl group with a carbon number between C1-C8, R3, R4, and R5 are each independently an alkyl group or alkoxy group with a carbon number between C1-C4, and at least one of R3, R4, and R5 is an alkoxy group, and preferably 2 or 3 of R3, R4, and R5 are alkoxy groups.

[0012] Aliphatic isocyanates have excellent weather resistance and yellowing resistance. The polyisocyanurate polymerized from them has a monocyclic or polycyclic structure. The six-membered ring structure of this isocyanurate is stable and has the characteristics of chemical resistance and excellent mechanical properties. The inventors found in their research that the copolymerization reaction of alkoxysilane monoisocyanate and aliphatic diisocyanate can introduce alkoxysilane in the form of chemical bonds on the basis of ensuring that the six-membered ring structure is not affected, which can effectively avoid migration out of the resin body, making the system have a stronger bonding effect than the introduction of traditional small molecule monosiloxane structure, which further improves the isocyanate composition and can be applied in many occasions.

[0013] In one embodiment of the present invention, the polyisocyanate composition comprises an aliphatic diisocyanate oligomer, a silicon-based isocyanurate monomer, a free aliphatic diisocyanate monomer and a free alkoxysilane monoisocyanate; preferably, in the polyisocyanate composition, the mass fraction of the silicon-based isocyanurate monomer is 1-30%, based on the total mass of the composition; preferably, the sum of the free aliphatic diisocyanate monomer and the free alkoxysilane monoisocyanate content is less than 1.0%.

[0014] In one embodiment of the present invention, the aliphatic diisocyanate is selected from C4-C6-1,1-diisocyanate having two terminal isocyanate groups and the isocyanate groups are not directly connected to the benzene ring. 30 The diisocyanate is preferably one or more of pentamethylene diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and methylcyclohexyl diisocyanate, and more preferably one or more of hexamethylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane diisocyanate.

[0015] In one embodiment of the present invention, the alkoxysilane monoisocyanate is selected from C1-C2- 10 Alkoxysilane, preferably one or more of the monoisocyanates in 3-isocyanatepropylmethyldiethoxysilane, 3-isocyanatepropylmethyldimethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-isocyanatebutyltrimethoxysilane, 3-isocyanatebutylmethyldimethoxysilane, 3-isocyanatebutylmethyldiethoxysilane, and 3-isocyanatebutyltriethoxysilane, more preferably 3-isocyanatepropyltrimethoxysilane and / or 3-isocyanatepropyltriethoxysilane.

[0016] Another object of the present invention is to provide a method for preparing a polyisocyanate composition containing a siloxane group.

[0017] A method for preparing a polyisocyanate composition containing a siloxane group, wherein the composition is the above-mentioned polyisocyanate composition, and the preparation method comprises the following steps:

[0018] The aliphatic diisocyanate and the alkoxysilane monoisocyanate react under a catalyst condition, the reaction is terminated to obtain an isocyanate mixture solution, and the unreacted aliphatic diisocyanate and the alkoxysilane monoisocyanate are removed to obtain a target polyisocyanate composition.

[0019] In one embodiment of the present invention, the reaction temperature is 50-150°C, preferably 100-135°C.

[0020] In one embodiment of the present invention, the catalyst is one or more of a halogen-containing quaternary phosphonium salt, a halogen-containing spirocyclic ammonium salt, and a metal alkoxide, preferably one or more of 5-nitrogenium-spiro[4.5]decane dihydrogen difluoride, zirconium tetra-n-pentoxide, (2-hydroxyethyl)triphenylphosphonium chloride, and tetrabutylphosphonium dihydrofluoride; preferably, the catalyst is added in an amount of 50-2000ppm, preferably 100-1000ppm, based on the total mass of the aliphatic diisocyanate and the alkoxysilane monoisocyanate. The catalyst can catalyze the self-polymerization of the aliphatic diisocyanate monomer to form an oligomer, and can also catalyze the hybridization polymerization of the aliphatic diisocyanate and the terminal isocyanate alkoxysilane, but has no obvious catalytic effect on the polymerization of the terminal isocyanate alkoxysilane itself.

[0021] In one embodiment of the present invention, the termination reaction is to add a terminator to terminate the reaction; preferably, the reaction is terminated when the polymerization conversion rate of the aliphatic diisocyanate reaches 35-65%, preferably 40-50%.

[0022] Another object of the present invention is to provide a use of a polyisocyanate composition containing a siloxane group.

[0023] A use of a polyisocyanate composition containing a siloxane group, wherein the composition is the above-mentioned polyisocyanate composition, or is a composition prepared by the above-mentioned preparation method, and the composition is used for coatings or adhesives, preferably for automotive coatings or adhesives, and more preferably for polyurethane automotive sealants.

[0024] Another object of the present invention is to provide a polyurethane automotive sealant.

[0025] A polyurethane automobile sealant, the sealant adopts the polyisocyanate composition or the composition prepared by the preparation method, and the sealant adopts the polyisocyanate composition containing siloxane as a curing agent.

[0026] The method for preparing automotive polyurethane sealant from isocyanate composition is well known in the art. For example, the present invention preferably adopts the following method to prepare polyurethane sealant from isocyanate composition: under the condition of 15-50°C and relative humidity below 35%, 40-80 parts of trifunctional polyether polyol A with molecular weight of 1000-6000 Dalton, 10-40 parts of difunctional polyether polyol B with molecular weight of 500-3000, 10-20 parts of carbon black filler are added to the glue making apparatus respectively, and 0.01-1% of any auxiliary agent and 0.01-1% of the total weight of polyether polyol A, B and carbon black filler are added. 200-1500ppm of amination catalyst is mixed evenly with mechanical stirring, and then the isocyanate composition containing siloxane groups is added in a metered amount according to the NCO / OH ratio of 1.0-1.05. The mixture is mixed evenly with mechanical stirring for 2-5 minutes, and the bubbles are removed by vacuuming at room temperature. The mixture is then poured into a standard mold. The mold can be placed with a glass or plastic substrate according to the situation. After pouring, it is cured at 80℃-120℃ for 0.5-3h, and then matured at room temperature for 12-48h to finally obtain a polyurethane sealant resin specimen.

[0027] For example, the polyether polyol is selected from at least one of polypropylene oxide ether polyol, polyethylene oxide ether polyol and polypropylene oxide-ethylene oxide ether copolymer polyol, preferably selected from at least one of polypropylene oxide ether polyol and polypropylene oxide-ethylene oxide ether polyol, more preferably selected from polypropylene oxide ether polyol.

[0028] For example, the initiator of the difunctional polyether polyol is a diol, such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, neopentyl glycol, trimethylpentanediol, cyclohexanedimethanol, 1,5-pentanediol or 1,6-hexanediol. The initiator of the trifunctional polyether polyol is a triol, such as trimethylolpropane, ethoxylated trimethylolpropane or glycerol.

[0029] For example, the auxiliary agent may be one or a mixture of any of the auxiliary agents such as a defoamer, a wetting agent, a dispersant, a leveling agent, and a silane coupling agent.

[0030] Compared with the prior art, the positive effects of the present invention are:

[0031] The composition of the present invention not only ensures that the product has the advantages of being solvent-free and having low viscosity, but can also significantly improve the construction efficiency and the comprehensive mechanical properties of the product. In particular, it is found that the product prepared by the composition has excellent performance stability under high temperature and high humidity environments, and is therefore particularly suitable for fields such as polyurethane sealants or automotive topcoats. DETAILED DESCRIPTION

[0032] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0033] The main raw materials and their sources in the following examples and comparative examples of the present invention are as follows:

[0034] Isophorone diisocyanate (IPDI), Wanhua Chemical Group Co., Ltd.;

[0035] Hexamethylene diisocyanate (HDI), Wanhua Chemical Group Co., Ltd.;

[0036] 3-isocyanatepropyltrimethoxysilane, purchased from Huaian Hongtu New Materials Co., Ltd.;

[0037] 3-isocyanatepropyltriethoxysilane was purchased from Huaian Hongtu New Materials Co., Ltd.;

[0038] 3-isocyanate butylmethyldimethoxysilane was purchased from Huaian Hongtu New Materials Co., Ltd.;

[0039] Zirconium tetrapentoxide, metal alkoxide catalyst, was purchased from Jianrui New Materials Co., Ltd.;

[0040] 5-Azonium-spiro[4.5]decane dihydrogen fluoride, a halogen-containing spirocyclic catalyst, was purchased from Aladdin Chemical Reagent Co., Ltd.;

[0041] Dioctyl phosphate, terminator, was purchased from Hangzhou Qianyang Technology Co., Ltd.;

[0042] T12, dibutyltin dilaurate, a commonly used urethanization catalyst for polyurethane resin, purchased from Nanjing Advant Co., Ltd.;

[0043] Wanol F3135, a polyether polyol commonly used in polyurethane sealants, with an average functionality of 3 and a molecular weight of about 5000 g / mol, is used as a reactive resin for isocyanate compositions for polyurethane sealants, from Wanhua Chemical Group Co., Ltd.;

[0044] Puranol D220, a polyether polyol commonly used in polyurethane sealants, with an average functionality of 2 and a molecular weight of about 2000 g / mol, used as a reactive resin for isocyanate compositions for polyurethane sealants, purchased from Jiahua Chemical Co., Ltd.;

[0045] AD-4810, composite additive for polyurethane sealant, purchased from Guangzhou Honghai New Material Technology Co., Ltd.;

[0046] Unless otherwise specified, the contents in the present invention are all by mass.

[0047] (1) NCO content test is carried out in accordance with GB / T 12009.4;

[0048] (2) Viscosity test: The dynamic viscosity at 25°C was measured using a Brookfield DT-2 viscometer.

[0049] (3) The method for analyzing the structure of silicon-based isocyanurate mononuclear body is as follows:

[0050] The AVANCE600 manufactured by Bruker FT-NMR was used, with deuterated chloroform (CDCl3) as solvent, and the sample (prepared isocyanurate product) was 5% by mass, 600 MHz, and scanned for 48 hours. 13 C nuclear magnetic resonance spectrum for qualitative analysis, wherein the carbon spectrum characteristic shifts of the six-membered ring structure of silicon-based isocyanurate shown in structure I prepared based on hexamethylene diisocyanate and 3-isocyanatepropyltrimethoxysilane were δ137.6ppm, δ152.7ppm, and δ155.8ppm, respectively.

[0051] (4) The mass fraction test method of silicon-based isocyanurate mononuclear structure (I) is as follows: the terminal isocyanate groups in the polyisocyanate composition are derivatized with methanol and analyzed by liquid chromatography-mass spectrometry (LC / MS). The configuration and test method are as follows:

[0052] (a) Sample preparation method: A certain amount of polyisocyanate composition is weighed and diluted with a stoichiometric excess of methanol, and the mixture is allowed to stand for three days to allow the existing isocyanate groups to completely react with methanol, thereby preparing a methanol derivative solution.

[0053] (b) Determination method:

[0054] The methanol derivative solution obtained above was measured using the following apparatus.

[0055] Agilent LC (liquid chromatograph), Agilent 1100 series

[0056] Column: Phenomenex, Kinetex 2.6μXB-C18 100A, (inner diameter 2.1 mm, length 50 mm)

[0057] Column temperature: 40°C

[0058] Detection: 205nm

[0059] Flow rate: 0.35mL / mins

[0060] Mobile phase: gradient of A and B solutions, A = water (0.05% formic acid), B = methanol

[0061] Injection volume: 2μL

[0062] Thermo MS (mass spectrometer)

[0063] Device: Thermo Electron, LCQ

[0064] Ionization: APCI

[0065] Mode: Positive

[0066] Scan range: m / z150~2000

[0067] The corresponding mass fraction is calculated from the integrated area of ​​the methanol adduct of structure (I).

[0068] (5) The sum of the free aliphatic diisocyanate monomer and the alkoxysilane monoisocyanate content was tested by establishing an external standard curve using high performance liquid chromatography (HPLC). The key parameters can be referred to as follows:

[0069] Chromatographic column: Waters XSelect HSS T3 5um 4.6*250mm;

[0070] Automatic sample injector: SIL-20A

[0071] Column temperature: 40°C

[0072] Injection volume: 10 μL

[0073] Detection wavelength: 281nm

[0074] Derivatization reagent: 4% 1-methoxyphenylpiperazine-acetonitrile solution.

[0075] The concentrations of the free aliphatic diisocyanate monomer and the alkoxysilane monoisocyanate are calculated based on their respective peak areas and external standard curves, and the sum of the two concentrations is taken as the sum of the contents of the free aliphatic diisocyanate monomer and the alkoxysilane monoisocyanate monomer in the polyisocyanate composition.

[0076] Example 1

[0077] Under an inert gas atmosphere, 1000 g of hexamethylene diisocyanate was first added to a reaction vessel and the temperature was raised to 105° C., and then 0.50 g of 5-nitrogenium-spiro[4.5]decane dihydrofluoride catalyst was added. At the same time, 3-isocyanatepropyltrimethoxysilane was added dropwise by continuous dropwise feeding, and a continuous polymerization reaction was carried out under the action of the catalyst. The continuous cumulative amount of 3-isocyanatepropyltrimethoxysilane was controlled to be 200 g for 50 minutes, and then the dropwise addition was stopped, and the reaction rate was maintained until the polymerization conversion rate of hexamethylene diisocyanate reached 65%. When the reaction mixture was stirred for 2 hours, 0.25 g of dioctyl phosphate terminator was added to terminate the reaction to obtain an isocyanate mixture solution, and unreacted hexamethylene diisocyanate and 3-isocyanatepropyltrimethoxysilane were further removed by distillation to obtain a polyisocyanate composition 1#. After analysis, the NCO content of the polyisocyanate composition was 14.0%, the sum of the free hexamethylene diisocyanate and 3-isocyanatepropyltrimethoxysilane monomer contents was 0.51%, the viscosity was 2875 cp / 25°C, and the mononuclear structure I content was 15.3%.

[0078] Example 2

[0079] Under an inert gas atmosphere, 1000 g of hexamethylene diisocyanate was first added to a reaction vessel and the temperature was raised to 110° C., and then 0.20 g of 5-nitrogenium-spiro[4.5]decane dihydrofluoride catalyst was added. At the same time, 3-isocyanatepropyltrimethoxysilane was added dropwise by continuous dropwise feeding, and a continuous copolymerization reaction was carried out under the action of the catalyst. The continuous cumulative amount of 3-isocyanatepropyltrimethoxysilane was controlled to be 200 g for 110 minutes, and then the dropwise addition was stopped. The reaction rate was maintained until the polymerization conversion rate of hexamethylene diisocyanate reached 35. %, 0.11 g of dioctyl phosphate terminator was added to terminate the reaction to obtain an isocyanate mixture solution, and unreacted hexamethylene diisocyanate and 3-isocyanatepropyltrimethoxysilane were further removed by distillation to obtain a polyisocyanate composition 2#. After analysis, the NCO content of the polyisocyanate composition was 18.1%, the sum of the free hexamethylene diisocyanate and 3-isocyanatepropyltrimethoxysilane monomer contents was 0.25%, the viscosity was 1839 cp / 25°C, and the mononuclear structure I content was 23.7%.

[0080] Example 3

[0081] Under an inert gas atmosphere, 1000 g of hexamethylene diisocyanate was first added to a reaction vessel and the temperature was raised to 105°C, and then 0.25 g of tetrapentanol zirconium catalyst was added. At the same time, 3-isocyanate butylmethyldimethoxysilane was added dropwise by continuous dropwise feeding, and a continuous copolymerization reaction was carried out under the action of the catalyst. The continuous cumulative amount of 3-isocyanate butylmethyldimethoxysilane was controlled to be 40 g for 80 minutes, and then the dropwise addition was stopped. The reaction rate was maintained until the polymerization conversion rate of hexamethylene diisocyanate reached 50%, and then 0. 12g of dioctyl phosphate terminator was added to terminate the reaction to obtain an isocyanate mixture solution, and unreacted hexamethylene diisocyanate and 3-isocyanate butylmethyldimethoxysilane were further removed by distillation to obtain a polyisocyanate composition 3#. After analysis, the NCO content of the polyisocyanate composition was 21.2%, the sum of the free hexamethylene diisocyanate and 3-isocyanate butylmethyldimethoxysilane monomer contents was 0.51%, the viscosity was 1612cp / 25°C, and the mononuclear structure I content was 2.8%.

[0082] Example 4

[0083] Under an inert gas atmosphere, 1000 g of isophorone diisocyanate was first added to a reaction vessel and the temperature was raised to 130° C. Then, 0.6 g of tetrapentanol zirconium catalyst was added. At the same time, 3-isocyanate propyl triethoxysilane was added dropwise by continuous dropwise feeding, and a continuous copolymerization reaction was carried out under the action of the catalyst. The continuous cumulative amount of 3-isocyanate propyl triethoxysilane was controlled to be 100 g for 80 minutes, and then the dropwise addition was stopped. The reaction rate was maintained until the polymerization conversion rate of isophorone diisocyanate reached 40%, and 0. The reaction was terminated by adding 33g of dioctyl phosphate terminator to obtain an isocyanate mixture solution, and the unreacted isophorone diisocyanate and 3-isocyanatepropyltriethoxysilane were further removed by distillation to obtain a polyisocyanate composition 4#. After analysis, the NCO content of the polyisocyanate composition was 21.0%, the sum of the free isophorone diisocyanate and 3-isocyanatepropyltriethoxysilane monomer contents was 0.80%, the viscosity was 4408cp / 25°C, and the mononuclear structure I content was 17.4%.

[0084] Comparative Example 1

[0085] Compared with Example 3, the only difference is that 3-isocyanatebutylmethyldimethoxysilane is not added.

[0086] Under an inert gas atmosphere, 1000 g of hexamethylene diisocyanate was first added to a reaction vessel and heated to 105 ° C, and then 0.25 g of tetra-n-pentanol zirconium catalyst was added, and a continuous polymerization reaction was carried out under the action of the catalyst until the polymerization conversion rate of hexamethylene diisocyanate reached 50%, and 0.12 g of dioctyl phosphate terminator was added to terminate the reaction to obtain an isocyanate mixture solution, and the unreacted hexamethylene diisocyanate was further removed by distillation to obtain a polyisocyanate composition 5#. After analysis, the NCO content of the polyisocyanate composition was 21.8%, the viscosity was: 2781 cP / 25 ° C, the mononuclear structure I content was 0, and the free hexamethylene diisocyanate content was 0.12%.

[0087] Comparative Example 2

[0088] Compared with Example 4, the only difference is that 3-isocyanatepropyltriethoxysilane is not added.

[0089] Under an inert gas atmosphere, 1000 g of isophorone diisocyanate was first added to a reaction vessel and heated to 130 ° C, and then 0.6 g of tetra-n-pentanol zirconium catalyst was added, and a continuous polymerization reaction was carried out under the action of the catalyst until the polymerization conversion rate of isophorone diisocyanate reached 40%, and 0.33 g of dioctyl phosphate terminator was added to terminate the reaction to obtain an isocyanate mixture solution, and the unreacted isophorone diisocyanate was further removed by distillation to obtain a polyisocyanate composition 6#. After analysis, the NCO content of the polyisocyanate composition was 16.9%, and the viscosity was:>30000 cP / 50 ° C, which needed to be diluted with butyl acetate before use, the content of mononuclear structure I was 0, and the content of free isophorone diisocyanate was 0.70%.

[0090] Preparation and application examples of polyisocyanate compositions.

[0091] At 25°C and a relative humidity of less than 35%, 50g of polyether polyol Wanol F3135, 30g of polyether polyol Puranol D220, 20g of carbon black filler, 0.2g of composite additive AD-4810 and 0.2g of dibutyltin dilaurate were added to a glue making container respectively, and after mechanical stirring and mixing evenly, isocyanate compositions 1-7# were added respectively according to an NCO / OH ratio of 1.07, and mechanical stirring was performed for 3-10 minutes to make them evenly mixed, and vacuum was drawn at room temperature to remove bubbles, and then the mixture was poured into a standard mold. Polyethylene terephthalate (PET, purchased from Toyobo, model number EcosyarVE500) was used as the substrate in the mold. The mixture was cured at 90°C for 2h and aged at room temperature for 24h to finally obtain a test sample.

[0092] (1) Peel strength test: The test sample was cut into sheets of 15 mm*200 mm and subjected to a 180° peel test at a test speed of 50 mm / min at 25°C using a tensile strength testing machine.

[0093] Evaluation criteria: Peel strength ≥ 10N / 15mm is excellent;

[0094] 6N / 15mm≤Peel strength≤10N / 15mm is good;

[0095] 1N / 15mm≤Peel strength≤6N / 15mm is poor;

[0096] (2) High temperature and high humidity hydrolysis resistance test: The test sample was cut into sheets of 15 mm*200 mm, placed in a pressure cooker, and treated at a high temperature and high pressure environment of 120°C and 0.1 MPa for 25 hours. After being taken out, it was aged at room temperature for 1 day, and then a 180° peel test was performed using a tensile strength testing machine at a test speed of 50 mm / min.

[0097] Evaluation criteria: Peel strength ≥ 10N / 15mm is excellent;

[0098] 6N / 15mm≤Peel strength≤10N / 15mm is good;

[0099] 1N / 15mm≤Peel strength≤6N / 15mm is poor;

[0100] (3) Weathering test: The test sample was cut into sheets of 50 mm*150 mm, and an accelerated aging test was performed on the composite layer using a xenon lamp weathering tester. The appearance after light aging was observed according to the ASTM G155 standard.

[0101] Evaluation criteria: No change is excellent;

[0102] Slight discoloration or cracks are good;

[0103] If there is obvious discoloration or cracks, it is considered poor;

[0104] (4) Peel strength test after illumination: The test sample was cut into sheets of 50 mm*150 mm, and the composite layer was subjected to an accelerated aging test using a xenon lamp weathering tester. According to the ASTM G155 standard, after the illumination, a 180° peel test was performed using a tensile strength testing machine at a test speed of 50 mm / min at 25°C.

[0105] Evaluation criteria: Peel strength ≥ 9N / 15mm is excellent;

[0106] 5N / 15mm≤Peel strength≤9N / 15mm is good;

[0107] 1N / 15mm≤Peel strength≤4N / 15mm is poor;

[0108] (5) Moisture and heat aging resistance test: The test specimens were cut into 15 mm*200 mm sheets and placed in a high temperature and high humidity test chamber. The experimental conditions were: humidity 85%, temperature 85°C, and time 1000 h. Moisture and heat aging resistance test was performed to observe whether the coating layer was powdered or had bubbles. The cross-hatch method was used to test adhesion. If more than 95% of the samples did not fall off, the samples were qualified. The rest were unqualified.

[0109] Table 1 Comprehensive performance test results of the samples of the embodiment and the comparative example

[0110]

[0111] As can be seen from Table 1, the test samples prepared in Examples 1-4 all showed excellent performance in terms of peel strength, peel strength after high-temperature and high-humidity aging, and weather resistance. The isocyanate composition has a low viscosity and does not require additional use of solvents. However, the test samples prepared in Comparative Examples 1-2 obviously have some poor indicators, and the comprehensive performance of the products is significantly reduced after high-temperature and high-humidity aging. In addition, some products need to be diluted with solvents due to their high viscosity, which is difficult to meet the actual working conditions.

[0112] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A polyisocyanate composition containing a siloxane group, characterized in that: The polyisocyanate composition comprises a silicon-based isocyanurate mononuclear structure formed by an aliphatic diisocyanate and an alkoxysilane monoisocyanate, such as Formula I: Among them, R1 is the residual group of aliphatic diisocyanate after removing the isocyanate group, R2 is an alkyl group with a carbon number between C1-C8, R3, R4, and R5 are each independently an alkyl group or alkoxy group with a carbon number between C1-C4, and at least one of R3, R4, and R5 is an alkoxy group, and preferably 2 or 3 of R3, R4, and R5 are alkoxy groups.

2. The composition according to claim 1, characterized in that The polyisocyanate composition comprises an aliphatic diisocyanate oligomer, a silicon-based isocyanurate mononuclear body, a free aliphatic diisocyanate monomer and a free alkoxysilane monoisocyanate; Preferably, in the polyisocyanate composition, the mass fraction of silicon-based isocyanurate mononuclear body is 1-30%, based on the total mass of the composition; Preferably, the sum of the free aliphatic diisocyanate monomer content and the free alkoxysilane monoisocyanate content is less than 1.0%.

3. The composition according to claim 1 or 2, characterized in that The aliphatic diisocyanate is selected from a C4-C6-containing isocyanate having two terminal isocyanate groups, and the isocyanate groups are not directly connected to the benzene ring. 30 The diisocyanate is preferably one or more of pentamethylene diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and methylcyclohexyl diisocyanate, and more preferably one or more of hexamethylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane diisocyanate.

4. The composition according to any one of claims 1 to 3, characterized in that The alkoxysilane monoisocyanate is selected from C1-C 10 Alkoxysilane, preferably one or more of the monoisocyanates in 3-isocyanatepropylmethyldiethoxysilane, 3-isocyanatepropylmethyldimethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-isocyanatebutyltrimethoxysilane, 3-isocyanatebutylmethyldimethoxysilane, 3-isocyanatebutylmethyldiethoxysilane, and 3-isocyanatebutyltriethoxysilane, more preferably 3-isocyanatepropyltrimethoxysilane and / or 3-isocyanatepropyltriethoxysilane.

5. A method for preparing a polyisocyanate composition containing a siloxane group, wherein the composition is the polyisocyanate composition according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The aliphatic diisocyanate and the alkoxysilane monoisocyanate react under a catalyst condition, the reaction is terminated to obtain an isocyanate mixture solution, and the unreacted aliphatic diisocyanate and the alkoxysilane monoisocyanate are removed to obtain a target polyisocyanate composition.

6. The preparation method according to claim 5, characterized in that: The reaction temperature is 50-150°C, preferably 100-135°C; And / or, the catalyst is one or more of halogen-containing quaternary phosphonium salts, halogen-containing spirocyclic ammonium salts, and metal alkoxides, preferably one or more of 5-azonia-spiro[4.5]decane dihydrogen fluoride, zirconium tetra-n-pentoxide, (2-hydroxyethyl)triphenylphosphonium chloride, and tetrabutylphosphonium dihydrofluoride; Preferably, the amount of catalyst added is 50-2000 ppm, preferably 100-1000 ppm, based on the total mass of aliphatic diisocyanate and alkoxysilane monoisocyanate; And / or, the termination reaction is to add a terminator to terminate the reaction; Preferably, the reaction is terminated when the polymerization conversion rate of the aliphatic diisocyanate reaches 35-65%, preferably 40-50%.

7. Use of a polyisocyanate composition containing a siloxane group, wherein the composition is the polyisocyanate composition according to any one of claims 1 to 4, or is a composition prepared by the preparation method according to claim 5 or 6, and the composition is used for coatings or adhesives, preferably for automotive coatings or adhesives, and more preferably for polyurethane automotive sealants.

8. A polyurethane automotive sealant, characterized in that: The sealant adopts the polyisocyanate composition according to any one of claims 1 to 4, or a composition prepared by the preparation method according to claim 5 or 6, and the sealant adopts the polyisocyanate composition containing siloxane as a curing agent.

Citation Information

Patent Citations

  • Preparing method of silane-modified polyurethane sealant

    CN105482758A

  • Organic silicon modified polyurethane sealant

    CN117384579A

  • Tripolymer in isocyanic ester class modified by silicane or functional polusiloxane, preparation method

    CN101050223A

  • Modified polyisocyanates mixed trimer curing agent containing monoisocyanate alkyl alkoxy silicane and preparation method thereof

    CN101186619A

  • Compound siloxane modified isocyanate tripolymer with high compatibility and low viscosity and preparation method thereof

    CN102093405A

Cited By

  • High-temperature-resistant polyurethane composition based on monochlorotrifluoropropene and preparation process of high-temperature-resistant polyurethane composition

    CN120118284A